2015
DOI: 10.1016/j.jcrs.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tear osmolarity on repeatability of keratometry for cataract surgery planning

Abstract: Drs. Epitropoulos, Matossian, Berdy, and Malhotra received compensation from Tearlab for participating in the study. No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 19 publications
3
128
0
8
Order By: Relevance
“…Consequently, it could impact on visual quality outcomes after IOL implantation or MCLs. It has also been reported that the variability in the keratometry readings is higher in patients with a tear osmolarity value higher than 316 mOsm/L that could have relevant influence on the IOL power calculation [20]. Ocular surface differences between women and men were also assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it could impact on visual quality outcomes after IOL implantation or MCLs. It has also been reported that the variability in the keratometry readings is higher in patients with a tear osmolarity value higher than 316 mOsm/L that could have relevant influence on the IOL power calculation [20]. Ocular surface differences between women and men were also assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The ocular surface changes related to ageing may adversely affect the optical quality of the eye and could have a detrimental effect on the success of these treatments. For example, in the case of IOL implantation, optimal pre-surgical ocular conditions are required in order to avoid risks such as severe DED, inaccurate IOL power estimation [20] and ocular discomfort after IOL [21]. Despite the fact that most of the research studies conducted until now have demonstrated that MCLs provide good visual quality results [17,[22][23][24][25][26][27], the prescription rate [28,29]) is low.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as dry eye can significantly affect the repeatability of keratometry measurements in cataract patients 19. This will also affect the calculation of SIA, as SIA is the preoperative to postoperative vector difference in corneal astigmatism; this will be the sum of the actual change in corneal astigmatism and any measurement errors.…”
Section: Discussionmentioning
confidence: 99%
“…Некоторые симптомы ССГ, в частности осмо-лярность слезы, могут иметь существенное значение для прогнозирования рефракционного результата, так как эти факторы определяют вариабельность показателей кератометрии [17]. При этом предопе-рационная терапия лубрикантами может оказаться полезной и сделать исходы рефракционной хирур-гии более прогнозируемыми.…”
Section: рис 3 соотношение пациентов с потребностью в пролонгированunclassified